Surface integrity of mild steel in die-sinking electrical discharge machine (EDM) - Muhamad Haniffah, Ghafar (2010)
A comprehensive study of the surface integrity of the machined workpiece in the electrical discharge machining (EDM) of mild steel (AISI 1020) is presented in this thesis. Copper Electrode was used as a tools in this research. EDM is a thermal process that uses spark discharge to erode electrically conductive materials, it’s primarily used for hard metals that very difficult to machine with traditional techniques. EDM tests on a mild steel workpiece were conducted on a sodick AQ55L (ATC) EDM Die-Sinking Machine. The surface Roughness tester Series Mahrsurf XR 20 is used to measure Ra and the surface microstructure was examined with a metallurgical microscopes. The EDM machining parameters those were used were peak current, IP (9A and 18A), discharge voltage (90V and 120V), servo voltage, SV (20V and 60V), pulse on-time (100μs and 300μs) and pulse off-time (500μs and 700μs). The full factorial design of experiment (DOE) from STATISTICA software was used to generate the arrangement of the experiment parameter and the software was used to analyze the effect of each parameter on the machining characteristics. From the analyzed result, peak current, IP and the pulse on-time have significant effect to the Surface Roughness, Ra. The lower values of these two parameters the lower Surface roughness, Ra observed. From the observation on the metallurgical microscopes, it is found there are clearly EDM damaged layer on the workpiece, distinguished by the width and length of microcrack and craters, especially at high peak current, IP and pulse on-time. The surface roughness, damaged layer and micro-cracks seem to decrease when the peak current and pulse on-time were set at very low values.